2011
DOI: 10.1055/s-0031-1279723
|View full text |Cite
|
Sign up to set email alerts
|

Injury Risk Evaluation in Sport Climbing

Abstract: The aim of this study was to quantify and rate acute sport climbing injuries. Acute sport climbing injuries occurring from 2002 to 2006 were retrospectively assessed with a standardized web based questionnaire. A total number of 1962 climbers reported 699 injuries, which is equivalent to 0.2 injuries per 1 000 h of sport participation. Most (74.4%) of the injuries were of minor severity rated NACA I or NACA II. Injury distribution between the upper (42.6%) and lower extremities (41.3%) was similar, with ligame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 24 publications
10
108
3
3
Order By: Relevance
“…Woollings, McKay and Emery (36) found 4 studies that estimated incidence rate in injuries/1000h climbing (1,17,21,27). We found an additional 6 studies that had data that had been used to estimate incidence rate.…”
Section: Incidence Ratementioning
confidence: 86%
See 1 more Smart Citation
“…Woollings, McKay and Emery (36) found 4 studies that estimated incidence rate in injuries/1000h climbing (1,17,21,27). We found an additional 6 studies that had data that had been used to estimate incidence rate.…”
Section: Incidence Ratementioning
confidence: 86%
“…Studies that have estimated the reported prevalence of injuries associated with rock climbing vary between 10% and 81% irrespective of cause; between 10% and 50% for impact injuries (9,11,17,37); between 28% and 81% for non-impact acute trauma injuries (9,11,18); and between 33% to 44% for chronic overuse injuries (1,9,37,38). Variance is likely to be 6 associated with differences in the nature, operational level of performance, frequency of performance and duration of activity between climbing disciplines.…”
Section: Prevalence and Incidence Of Injuriesmentioning
confidence: 99%
“…Killian et al [75] found a significant correlation between the incidence of ankle sprains and bouldering as well as in between ankle sprains and sport climbing. Neuhof et al [2] in contrast found a even injury distribution between the upper (42.6%) and lower extremities (41.3%) (Figure 1). In summary, most of the studies found that overuse injuries are mainly affecting the upper extremity, while acute traumatic injuries are more frequently located on the lower extremity [1,76] .…”
Section: Et Al Feet Injuries In Rock Climbersmentioning
confidence: 87%
“…So far, most research indicates that the upper extremity to be the most injured body region in non-alpine rock-climbing [2,3,5,6,10,14,15,40,60,[64][65][66][67][68][69][70][71][72] . Schöffl et al [61] analysed 604 injured climbers (sport climbing, indoor climbing) and reported 247 of 604 (40.9%) injuries involved the hand, 9.1% the foot.…”
Section: Et Al Feet Injuries In Rock Climbersmentioning
confidence: 99%
See 1 more Smart Citation